APPROXIMATIONS TO PERFORMANCE MEASURES IN QUEUING SYSTEMS - Kambo, N. S.; Rangan, A.; Moghimihadji, E. (Southern African Inst Industrial Engineering, 2012)
Approximations to various performance measures in queuing systems have received considerable attention because these measures have wide applicability. In this paper we propose two methods to approximate the queuing characteristics of a GI/M/1 system. The first method is non-parametric in nature, using only the first three moments of the arrival distribution. The second method treads the known path of approximating the arrival distribution - by a mixture of two exponential distributions - by matching the first three moments. Numerical examples and optimal analysis of performance measures of GI/M/1 queues are provided to illustrate the efficacy of the methods, and are compared with benchmark approximations.
Keywords: Gi/M/1 Queue; Mixtures